2013
DOI: 10.1111/ped.12080
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of anesthetic management for children with craniofacial deformities

Abstract: A successful outcome depended on the provision of interdisciplinary craniofacial team management, comprehensive anesthetic evaluation and management, well-informed and cooperative children and supportive family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The common types of facial cle s encountered in clinical anesthesia practice are described in Table 1. [9][10][11] The common types of craniofacial cle s encountered are described in Table 2.…”
Section: Craniofacial Cleftsmentioning
confidence: 99%
“…The common types of facial cle s encountered in clinical anesthesia practice are described in Table 1. [9][10][11] The common types of craniofacial cle s encountered are described in Table 2.…”
Section: Craniofacial Cleftsmentioning
confidence: 99%
“…These could lead to complications of respiratory problems, vision, cleft palate and hearing loss [ 6 ]. A retrospective study of 45 children in 2005-2009 with craniofacial deformities revealed that children with TCS had the most difficult airway management with DL view, often requiring multiple airway accessories and intubation techniques [ 7 ]. The two most common methods of airway management used were stylet and fiberoptic intubation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 45 children in 2005-2009 with craniofacial deformities revealed that children with TCS had the most difficult airway management with DL view, often requiring multiple airway accessories and intubation techniques [ 7 ]. The two most common methods of airway management used were stylet and fiberoptic intubation [ 7 ]. Another retrospective study on TCS children showed that 53% of the 97 cases had modified Cormack Lehane (MCL) view grade 3 and grade 4 DL and failed intubation rate of 5% in 123 cases and that their MCL views become more difficult with increasing age [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was very rapidly completed at the first attempt, maintaining the patient in spontaneous breathing, and the armed orotracheal tube was correctly positioned. During surgery any other anesthetic complication was not observed [ 14 ].…”
Section: Case Reportmentioning
confidence: 99%